Optimizing the Strategic Communication of Gerbas Tani Community in Developing Tourist Village in Kedungrejo, Rowokangkung, Lumajang - Alhimni Fahma; Achmad Arifulin Nuha (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2023)
Gerbas Tani stands for Gerakan Belanja Sayur dari Lahan Petani, which was born in 2018, marked by the educational activity